Thymoquinone, as a Novel Therapeutic Candidate of Cancers - Belal Almajali; Hamid Ali Nagi Al-Jamal; Wan Rohani Wan Taib; Imilia Ismail; Muhammad Farid Johan; Abd Almonem Doolaanea; Wisam Nabeel Ibrahim (MDPI AG, 2021)
To date, natural products are widely used as pharmaceutical agents for many human diseases and cancers. One of the most popular natural products that have been studied for anticancer properties is thymoquinone (TQ). As a bioactive compound of Nigella sativa, TQ has shown anticancer activities through the inhibition of cell proliferation, migration, and invasion. The anticancer efficacy of TQ is being investigated in several human cancers such as pancreatic cancer, breast cancer, colon cancer, hepatic cancer, cervical cancer, and leukemia. Even though TQ induces apoptosis by regulating the expression of pro- apoptotic and anti-apoptotic genes in many cancers, the TQ effect mechanism on such cancers is not yet fully understood. Therefore, the present review has highlighted the TQ effect mechanisms on several signaling pathways and expression of tumor suppressor genes (TSG). Data from relevant published experimental articles on TQ from 2015 to June 2020 were selected by using Google Scholar and PubMed search engines. The present study investigated the effectiveness of TQ alone or in combination with other anticancer therapeutic agents, such as tyrosine kinase inhibitors on cancers, as a future anticancer therapy nominee by using nanotechnology.